Analisis Kelayakan Usaha Toko Roti di Kecamatan Taman Kabupaten Sidoarjo - Sakti Danadyaksa Adi Wardhana; Parikesit Penangsang (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
Seeing the large interest and need of the Indonesian population for bread, there is a possibility for a larger bakery business. Therefore, it is not surprising that many people are interested in trying their luck by becoming bakery business owners. However, some people do not understand the feasibility level, so prospective business actors are still hesitant to open a bakery business. Therefore, the research focuses on analyzing the feasibility of a bakery business in Taman District, Sidoarjo Regency. In this research, 6 bakery business operators in the villages of Wage, Geluran and Bangah were used as informants. This type of research is descriptive research. Research data was obtained through informant interviews and analyzed using business financial feasibility in the form of R/C, B/C, and ROI. The research results showed that the average R/C value was 2.16, the average B/C value was 1.16 and the average ROI value was 41.03%. All the results show that the bakery business in Taman District, Sidoarjo Regency is feasible to run.